(untitled) (Historia, 2021)
Mohamed Adhikari’s collection is at the cutting edge of genocide studies. It represents the efforts of a group of scholars from across the globe to revise an outdated, crude and phenomenologically useless model of genocide as simply an ideological crime, defined only by mass killing. This is an image largely based itself on a crude rendering of the Holocaust. In its place we have a complex reorienting of genocide as a process inextricably linked to colonialism. Or to put it another way, in our increasingly global age it forces us to think about the historic and indeed ongoing links between genocide and globalisation. As such, this is an urgent work that demands our attention.